2022
DOI: 10.4081/ijwc.2022.90
|View full text |Cite
|
Sign up to set email alerts
|

Studio di valutazione del presidio Rigenoma con ozoile nel trattamento di lesioni cutanee croniche

Abstract: L’ozono è utilizzato per fini medici sin dall’800 e da anni anche per il trattamento delle lesioni cutanee. Le proprietà di questa molecola sono molteplici, tra cui aumento della disponibilità di O2, antinfiammatorie ed antisettiche. Abbiamo testato la perfomance di un presidio a base di Ozoile (Ozonidi stabili da olio di oliva biologico), nel trattamento di lesioni cutanee croniche. Sono stati reclutati 40 pazienti con lesioni di diversa etiologia e localizzazioni alla gamba o al piede. I parametri analizzati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…As you can see from the image at the end of this section, the idea for a simple classification was based primarily on the severity and presentation of initial clinical findings and it was useful to quickly document the severity of the condition. 18 …”
Section: Methodsmentioning
confidence: 99%
“…As you can see from the image at the end of this section, the idea for a simple classification was based primarily on the severity and presentation of initial clinical findings and it was useful to quickly document the severity of the condition. 18 …”
Section: Methodsmentioning
confidence: 99%
“…Ozoile showed a decrease in LPS-induced inflammatory response in colonic epithelial cells and THP-1 monocytes [17]. Furthermore, in another study on patients with phlebostatic leg ulcers, Ozoile was shown to stimulate fibroblast proliferation and neoangiogenesis [18,19]. While the beneficial effects of Ozoile have been reported, in these studies no cytotoxic effects or sensitization with allergic reactions are described.…”
Section: Introductionmentioning
confidence: 99%